2020
DOI: 10.1186/s12886-020-01707-3
|View full text |Cite
|
Sign up to set email alerts
|

OCT angiography analysis of retinal vessel density in primary open-angle glaucoma with and without Tafluprost therapy

Abstract: Background Primary open-angle glaucoma (POAG) is a progressive neurodegenerative disease which leads to irreversible blindness. An elevated intraocular pressure (IOP) is considered to be the main risk factor for the disease progression. It is known that retinal blood flow is altered in POAG eyes. Tafluprost, a prostaglandin analogue which lowers the IOP, has shown to also improve the retinal blood flow in animals. Methods The current study therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Given that the RPC is damaged with glaucoma progression ( 19 ), those in need of surgery may have impaired regulation patterns of retinal microcirculation compared to healthy controls or early-stage patients. It was reported that prostaglandin analog could improve retinal microcirculation ( 15 , 17 , 41 ), but the exact role of its interaction on IOP and microcirculation was not thoroughly studied. The pharmacological effect can't be completely ruled out unless further studies compare different doses or categories of IOP-lowering medication.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the RPC is damaged with glaucoma progression ( 19 ), those in need of surgery may have impaired regulation patterns of retinal microcirculation compared to healthy controls or early-stage patients. It was reported that prostaglandin analog could improve retinal microcirculation ( 15 , 17 , 41 ), but the exact role of its interaction on IOP and microcirculation was not thoroughly studied. The pharmacological effect can't be completely ruled out unless further studies compare different doses or categories of IOP-lowering medication.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have presented an improvement in OCT angiography parameters after IOP lowering treatment [ 7 , 8 , 9 , 10 , 11 ], whereas others have not [ 12 , 13 , 14 ]. Moreover, even though medical IOP reduction is the most common initial choice for treating glaucoma, only a few studies have focused on the effect of it [ 7 , 8 , 15 ]. A cross-sectional retrospective study by Lin et al shows that for NTG participants the different topical medications, including dorzolamide, carteolol and brimonidine, have different impacts on peripapillary superficial retinal VD and RNFL [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have revealed an improvement in OCT angiography parameters after IOP reduction treatment [ 7 , 8 , 9 , 10 , 11 ], whereas others have not [ 12 , 13 , 14 ]. Moreover, most studies have focused on the effect of surgical IOP reduction [ 10 , 11 , 13 , 14 ] instead of medical IOP reduction [ 7 , 8 , 15 ], which is the most common initial choice for treating glaucoma. A prospective investigation of the changes in the ocular microvasculature induced by IOP-lowering medications may help to clarify the effect of long-term IOP reduction treatments on glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…Weindler et al [ 46 ] used OCT-A (Topcon DRI OCT Triton) to compare the effect of topical tafluprost or surgical treatment on ONH blood flow density in patients with POAG. The flow density of patients with POAG who underwent IOP-lowering surgery (deep sclerectomy, trabeculotomy, and trabeculectomy) because of poor compliance or intolerance to multiple eye drops was used for comparison.…”
Section: Clinical Researchmentioning
confidence: 99%